Mechanical separation process for the value enhancement of Atlantic horse mackerel (Trachurus trachurus), a discard fish. (February 2017) - Secci, Giulia; Borgogno, Monica; Mancini, Simone; Paci, Gisella; Parisi, Giuliana
Abstract: Mechanically separated meat (MSM) is the product obtained by removing meat from bones by pressure application. Whole fillets and fish burgers from minced muscle and from mechanical separation of Atlantic horse mackerel ( Trachurus trachurus ) were evaluated immediately after processing (T0 ) and after 90 days of storage at − 20 °C for parameters related to quality loss. Firstly, mechanical separation inhibited water losses (2.67% against 4.57 and 5.57% in whole fillets and burgers from minced muscle, respectively), but the colour of MSM was duller and redder than the samples from other groups. Horse mackerel contained low fat (< 1 g/100 g muscle), and high PUFAω3 content (around 57 g/100 g total fatty acids), especially EPA and DHA (around 52 g/100 g) regardless the treatment. However, the species was susceptible to oxidation, as revealed by the high TBARS content at T0 (> 8 mg MDA-eq/100 g muscle). Nevertheless, Atlantic horse mackerel showed a high antioxidant capacity (ABTS, 2, 2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid, DPPH, 2, 2-diphenyl-1-picrylhydrazyl, and FRAP, ferric-reducing ability) at T0 which may protect muscle against oxidative damages both during processing treatment and storage. Industrial relevance: The mechanical separation process described in the article has been largely utilized for terrestrial animal products. However, it is seldom adopted by fish industry, especially for recovering discard fish species. Horse mackerel is an underutilized species, normally transformed into animal feed despite its high levels of omega-3 polyunsaturated fatty acids. Therefore this study was conducted in order to determine the effect of a mechanical separation technique on the physicochemical properties of horse mackerel. Our study showed that, although this species is susceptible to oxidative changes, mechanically separate meat can be a high-quality ingredient in burgers, nuggets, sticks, or even sauces which may represent a way for the valorisation of discard species. Highlights: Mechanical separation technology was applied on horse mackerel. The benefit and limitations of the mechanical separation technique were described. Mineral and fatty acid composition, antioxidant capacity and oxidative status were evaluated. Mechanically separated meat from discard fish could be a high quality ingredient.